Childhood Trauma and Cyberbullying Perpetration: The Mediating Role of Callous-Unemotional Traits - Silva, Sofia (Victims & offenders, 2025)
Throughout the years, cyberbullying has been explored and connected to experiences of childhood trauma (CT) and high levels of callous-unemotional (CU) traits. This study aims to explore differences between cyberbullying perpetrators and non-perpetrators and explore the mediate role of CU traits between CT and cyberbullying perpetration (CBP). A cross-sectional study was conducted with 7139 participants (3728 girls; 52.2%), aged 10–22 years, of whom 276 (59.8% male) self-reported cyberbullying perpetration. Propensity score matching was used to select a sample of 276 adolescents’ non-perpetrators with similar characteristics, in order to compare cyberbullying perpetrators with non-perpetrators. Results showed that CBP was more predominant among boys and middle adolescents. Callousness trait partially mediates the relation between all the studied dimensions of CT and CBP. Uncaring traits partially mediated the relation between emotional, physical, and sexual abuse. CU traits (i.e., callousness and uncaring) mediated the relation between physical, and sexual abuse, and physical and emotional neglect. This study gives a better understanding of the underlying mechanisms of the relation between CT and CBP, which allows professionals to have a different evaluation when considering intervention programs.